Effects of castor oil on Saccharomyces cerevisiae growth and activities during batch anaerobic fermentation - Huang, Chai Hung (Universiti Malaysia Sarawak (UNIMAS), 2014)
Saccharomyces cerevisiae is the most effective and safest microorganism in ethanol fermentation by involving sugar as substrate. It has many unique properties including fast growth rate, efficient glucose repression, efficient ethanol production and a tolerance for environment stresses such as high ethanol concentration. However, the growth and fermentative activities of yeast cell is inhibited by ethanol that accumulates in fermentation broth. It is because high concentration of ethanol is toxic to the yeast cell. Therefore, ethanol produced should be removed from fermentation broth. This study emphasized on the effects of castor oil on S. cerevisiae growth and activities during batch anaerobic fermentation. As performed by preliminary studies, castor oil has its capability to acts as selective ethanol-water separator. Four different glucose concentrations with and without castor oil were examined for optimum glucose concentration, in term of yeast's growth and ethanol production. Based on the results, the optimum glucose concentration for effective ethanol production was 10% glucose concentration. Almost-all glucose (100.00 g/1) was consumed by 8.05 x 10° cell/ml of yeast cell and converted into 86.27% Theoretical Ethanol Yields. Furthermore, the survival of S. cerevisiae in broth with castor oil was higher than broth without castor oil, where 8.05 x 10° cell/ml was higher than 6.20 x 10° cell/ml at 72 hours. Meanwhile, ethanol yield in broth with castor oil was lower than broth without castor oil due to the absorption of ethanol by castor oil. It can lead to the reduction of ethanol and indirectly reduce the toxicity of ethanol to the yeast cell. Hence, castor oil was assistance to the growth and ferrnentative activities of S. cerevisiae.